ChemInform Abstract: Rhodium‐Catalyzed Enantioselective Intramolecular C—H Silylation for the Syntheses of Planar‐Chiral Metallocene Siloles. Issue 39 (September 2015) - Zhang, Qing‐Wei; An, Kun; Liu, Li‐Chuan; Yue, Yuan; He, Wei
Abstract The absolute configuration of compound (IIb) is determined to be Spl by X‐ray analysis.